Implementing and Evaluating a Fellowship for Community-Based Physicians and Physician Assistants: Leadership, Practice Transformation, and Precepting. Issue 2 (2022) - Casola, Allison R.; Cunningham, Amy; Crittendon, Denine; Kelly, Samantha; Sifri, Randa; Arenson, Christine
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Formal training in practice transformation, leadership, clinical education, and/or the time to gain these skills are limited postresidency for primary care physicians and physician assistants. Therefore, we created a novel Primary Care Champions fellowship program that provides practical experiences in education, practice transformation, and leadership for primary care physicians and physician assistants in community practice. The purpose of this study is to describe the fellowship and evaluate feedback from the first cohort. Methods: In the Jefferson Primary Care Champions Fellowship, fellows are provided protected time from clinical obligations to engage in didactic, informal, and experiential learning. They meet monthly and participate in student precepting training and receive mentorship from senior clinician administrators, scientists, educators, and population health researchers to hone skills for leadership and practice transformation endeavors. Cohort one began in September 2018. All fellows were family physicians from community-based practices in Philadelphia, PA (N = 4) and selected in collaboration with their practice leadership. Mixed-methods postprogram evaluations included Organizational Readiness Assessment and qualitative feedback. Results: Fellows denoted individual time, small-group mentorship, protected project time, and open-robust discussions about primary care most useful. Three fellows reported that they plan to continue their practice-improvement projects postfellowship and one published her initial project findings and reflections. Discussion: Overall feedback from the first cohort was positive. Fellows greatly appreciated structured time to explore primary care interests, contemplated long-term career prospects, and considered leadership opportunities. Cohort two is currently underway and cohort three is in recruitment.